Burden of Noise-Induced Hearing Loss among Rice Mill Workers in Sokoto State, Northwest Nigeria - Azees, Ayotunde; Ango, Jessica; Isa, Abdulfattah; Adeniyi, Makinde (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Work heavily impacts workers’ health globally, with noise-induced hearing loss (NIHL) increasingly becoming a major public health concern.Aim:This study accessed the prevalence and predictors of noise-induced hearing impairment among local rice mill workers in Sokoto State, Northwest Nigeria.Materials and Methods:This cross-sectional study was conducted among rice mill workers between June 2019 and July 2019. Participants were selected using a multistage sampling technique, and a pretested interviewer-administered questionnaire was used for data collection. Data were analyzed using IBM®Statistical Package for the Social Sciences (SPSS) version 22, and the results were presented in tables and figures. Statistical tests of associations were conducted using the Chi-square test and binary logistic regression with a significance level set atP< 0.05.Results:The noise level in the rice mills ranged from 81.8 dBA to 91.7 dBA, with a mean of 86.7 ± 2.3 dBA. A hundred and eighty-five respondents (46.5%) of the 398 respondents had at least a symptom of hearing loss, with tinnitus (145 (36.4%)) being the most prevalent. About a third of 125 (32.5%) had hearing impairment in at least one of the ears on audiometry. The predictors of hearing impairment on audiometry were cigarette smoking, education, and having symptoms of hearing loss.Conclusion:The burden of noise-induced hearing impairment is high among rice mill workers in Sokoto State, Northwest Nigeria; hence, both the government and rice mill owners need to initiate smoking cessation programs, promote the use of personal protective equipment, and urgently implement hearing conservation programs to address the problem.